การพัฒนาสมรรถนะของนักบริหารและพัฒนาเมืองตามความต้องการของ องค์กรปกครองส่วนท้องถิ่น : ศึกษากรณี จังหวัดปทุมธานี - ชุมวรฐายี, ณัฐศรัณย์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
การพัฒนาสมรรถนะของนักบริหารและพัฒนาเมืองตามความต้องการขององค์กรปกครองส่วนท้องถิ่น มีวัตถุประสงค์เพื่อศึกษาระดับความต้องการการพัฒนาสมรรถนะของนักบริหารและพัฒนาเมืองตามความต้องการขององค์กรปกครองส่วนท้องถิ่น เพื่อพัฒนารูปแบบการบูรณาการการเรียนการสอนกับการพัฒนาสมรรถนะของนักบริหารและพัฒนาเมือง และเพื่อบูรณาการการเรียนการสอนกับการพัฒนาสมรรถนะของนักศึกษาสาขาวิชาการบริหารและพัฒนาเมือง กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ คณะผู้บริหารและบุคลากรของเทศบาลนครรังสิต เทศบาลเมืองบึงยี่โถ และองค์การบริหารส่วนตำบลคลองสาม จำนวน 181 คน เครื่องมือที่ใช้ในการวิจัย คือ 1) แบบสัมภาษณ์แบบมีโครงสร้าง เพื่อเก็บข้อมูลจากผู้บริหาร 2) แบบสอบถามแบบมาตราส่วนประมาณค่า เพื่อเก็บข้อมูลจากเจ้าหน้าที่ 3) แบบประเมินความเหมาะสม ของรูปแบบ การวิเคราะห์ผลโดยใช้โปรแกรมสำเร็จรูปทางสถิติเพื่อหาค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ข้อมูลเชิงคุณภาพใช้ การวิเคราะห์เนื้อหา ผลการวิเคราะห์ระดับความต้องการการพัฒนาสรรถนะของนักบริหารและพัฒนาเมืองด้านสมรรถนะ พบว่าระดับความต้องการการพัฒนาสมรรถนะของนักบริหารและพัฒนาเมืองขององค์กรปกครองส่วนท้องถิ่น จังหวัดปทุมธานี ทั้ง 3 สมรรถนะ ได้แก่ สมรรถนะส่วนบุคคล อยู่ในระดับมาก สมรรถนะหลัก อยู่ในระดับมาก และสมรรถนะสายงาน อยู่ในระดับปานกลาง สามารถนำมาบูรณาการในการจัดการเรียนการสอนเพื่อพัฒนาสมรรถนะในแต่ละด้าน เช่น วิชาระบบสารสนเทศเพื่อการบริหาร วิชาการพัฒนาทักษะทางภาษาอังกฤษ วิชาการวิเคราะห์โครงการและการบริหารโครงการ และแนวทางบูรณาการการพัฒนาสมรรถนะของนักบริหารและพัฒนาเมืองกับการเรียนการสอน เช่น จัดทำแผนปฏิบัติการฝึกภาคสนามร่วมกับองค์กรปกครองส่วนท้องถิ่น The objectives of the research were to study the degree of demand in competency development of urban development and administrators on the local administrative organization, to develop the integration model of learning and teaching to develop the competency of the urban administrators, and to integrate learning and teaching related to the competency development of the student in administration program. The research collected data from 181 samples who are the administrators and personel of Rangsit Municipality, Bueng Yitho Municipality and Khlong Sam Subdistrict Administrative Organization. The tool used for collecting data were 1) the structured interview to collect from the administrators, 2) the rating scale to collect from the officers, and 3) the evaluation form. The assessment of the suitability of the model, the SPSS program is used in analyzing the data to find frequency, percentage, mean, and standard deviation. The content analysis was used to analyze the qualitative data. The results of research were found that : 1.The demand in competency development of urban development and administrator includes three competencies: Personal competencies, Core Competencies are high and Functional Competencies were moderate. This can integrated the management of learning and teaching in each competency. Personal competencies have the course in administration and urban development program that can bring to integrate learning and teaching as follows: the subject of management information system, the subject of skill development for English language and the subject of project management and analysis, The synthetic result of competency development of urban development administrators can integrated with learning and teaching such as, the cooperation in fieldwork training with the local administrative organization.